Congenital Supravalvar Mitral Ring - A Case Report - Raquel Reis Soares; Leonardo Ferber; Matheus Ferber; Daniel Soares Mata (Brazilian Journal of Cardiovascular Surgery)
Abstract Congenital mitral valve stenosis is a rare and severe disease, usually associated with other heart defects. The appropriate intervention depends on the site and mechanism of valvular obstruction and the aim is to avoid or delay valve replacement since it is associated with significant morbidity and mortality. Early single-stage complete repair is associated with better prognosis. We report the case of a 20-month-old child with a supravalvar mitral ring combined with a ventricular septal defect; pulmonary arterial systolic pressure before the surgery was 79 mmHg. The patient underwent a successful surgical repair with good clinical resolution.